The procrastination economy : the big business of downtime - Tussey, Ethan (New York University Press, 2018)
In moments of downtime - waiting for a friend to arrive or commuting to work - we pull out our phones for a few minutes of distraction. Just as television reoriented the way we think about living rooms, mobile devices have taken over the interstitial spaces of our everyday lives. Ethan Tussey argues that these in-between moments have created a procrastination economy, an opportunity for entertainment companies to create products, apps, platforms, subscription services, micropayments, and interactive opportunities that can colonize our everyday lives. But as businesses commoditize our free time, and mobile devices become essential tools for promotion, branding and distribution, consumers are using these devices as a means of navigating public and private space. These devices are not just changing the way we spend and value our time, but also how we interact with others and transform our sense of the politics of space. By examining the four main locations of the procrastination economy - the workplace, the commute, the waiting room, and the "connected" living room - Ethan Tussey illuminates the relationship between the entertainment industry and the digitally empowered public. --